(untitled) - Motohashi, Kazuyuki (Tokyo, 2015)
This book presents theories and case studies for corporations in developed nations, including Japan, for designing strategies to maximize opportunities and minimize threats in business expansion into developing nations. The case studies featured here focus on Asia, including China and India, and use examples of Japanese manufacturers. Five case studies are provided, including Hitachi Construction Machinery and Shiseido in China and Maruti Suzuki in India. These cases facilitate the reader’s understanding of the business environments in emerging economies. This volume is especially recommended for businesspeople responsible for international business development, particularly in China and India. In addition, the book serves as a useful resource for students in graduate-level courses in international management.
Keywords: International business enterprises,Doanh nghiệp kinh doanh quốc tế